Stepping Towards Transformation: Student Political Awareness through Instruction the Development of the 21st Century Political Education Curriculum - Sunarso; Nasiwan; Suharno; Hidayah, Yayuk; Saputro, Johan Dwi (Mimbar Ilmu, 2024)
Contribution in directing the transformation of political education to prepare more informed and politically engaged citizens in the 21st century. This study aims to analyze the political awareness index of students through teaching in the development of the 21st century political education curriculum. The research method used was a quantitative survey involving respondents from the student population. Respondents were randomly selected using a simple random sampling technique. Data were collected using questionnaires that have been prepared based on conceptual frameworks relevant to research variables. The collected data is then statistically analyzed using descriptive methods and inferential analysis to identify significant relationships and patterns between the variables studied. The results of this study are expected to provide a deeper understanding of the Student Political Awareness Index and the role of teaching in the development of the 21st century political education curriculum in shaping student political awareness. Through this article, it can be concluded that the Student Political Awareness Index and the role of teaching in the development of the 21st century political education curriculum in shaping student political consciousness.